Memory Properties in Cloud‐Resolving Simulations of the Diurnal Cycle of Deep Convection. (8th August 2020) - Daleu, C. L.; Plant, R. S.; Woolnough, S. J.; Stirling, A. J.; Harvey, N. J.
Abstract: A series of high‐resolution three‐dimensional simulations of the diurnal cycle of deep convection over land are performed using the new Met Office NERC cloud‐resolving model. This study features scattered convection. A memory function is defined to identify the effects of previous convection in modifying current convection. It is based on the probability of finding rain at time t 0 and at an earlier time t 0 −Δ t compared to the expected probability given no memory. The memory is examined as a function of the lag time Δ t . It is strongest at gray‐zone scales of 4–10 km, there is a change of behavior for spatial scales between 10 and 15 km, and it is reduced substantially for spatial scales larger than 25 km. At gray‐zone scales, there is a first phase of the memory function which represents the persistence of convection and it is maintained for about an hour. There is a second phase which represents the suppression of convection in regions which were raining 1 to 3 hr previously, and subsequently a third phase which represents a secondary enhancement of precipitation. The second and third phases of the memory function develop earlier for weaker forcing. When thermodynamic fluctuations resulting from the previous day are allowed to influence the development of convection on the next day, there are fewer rainfall events with relatively large sizes, which are more intense, and thus decay and recover more slowly, in comparison to the simulations where feedback from previous days is removed. Further sensitivity experiments reveal that convective memory attributed to these thermodynamic fluctuations resides in the lower troposphere. Plain Language Summary: Identifying the effects of previous convection in modifying the subsequent development of convection is important for correctly capturing the large‐scale effects of moist convection (convective parameterization) in numerical models used for weather forecasts and climate prediction. We evaluate these memory effects from idealized cloud‐resolving model simulations of the diurnal cycle of scattered convection. We find that the main convective systems persist for about an hour. Later, convection is suppressed in those regions which were raining 1 to 3 hr previously, and later still there is a secondary enhancement of convection in the regions that were previously suppressed. These memory effects are sensitive to the size of the region over which they are evaluated: they are small for length scales coarser than 50 km but become increasingly important at scales of 10 km or less. At these finer scales they are inconsistent with the diagnostic assumptions made in many current convective parameterization schemes. We also investigated the effects of the previous day's convective activity on that of the next day, in particular through the effects on spatial variability of temperature and moisture in the lower troposphere. If the variability associated with the previous day is artificially removed, then the convective systems become numerous but less intense. They are found to be smaller and to decay more rapidly, with a more rapid recovery of the atmosphere in their vicinity. Key Points: The effetcs of previous convection in modifying current development of convection is strongest at gray‐zone scales of 4 to 10 km Rain cores become more intense when thermodynamic fluctuations from previous day influence the evolution of convection on the next day Convective memory attributed to thermodynamic variability resulting from previous diurnal cycle mostly resides in the lower troposphere